2017
DOI: 10.5147/ajpb.v1i3.111
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci (QTL) that Underlie SCN Resistance in Soybean [Glycine max (L.) Merr.] PI438489B by ‘Hamilton’ Recombinant Inbred Line (RIL) Population

Abstract: Soybean cyst nematode caused by Heterodera glycines Ichinohe is the most devastating pest in soybean [Glycine max (L.) Merr.]. Resistance to SCN is complex, polygenic, race and cultivar specific, and it is controlled by several quantitative trait loci (QTL). Our objective was to identify and map QTL for SCN resistance to races 3 (HG Type 0) and 5 (HG Type 2.5.7) using a high density SNP-based genetic linkage map based on the PI438489B by ‘Hamilton’ (PIxH, n=50) recombinant inbred line population. The PI438489B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The precisely identifying and positioning of QTL are crucial for successful MAS. Up to now, many QTL associated with SCN resistance have been effectively tagged with different molecular marker systems, including SSR, RAPD, RFLP and SNP [ 12 , 14 , 19 , 46 48 ]. However, no sequencing based mapping like GWAS for QTL or genes underlying the resistance to SCN has been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…The precisely identifying and positioning of QTL are crucial for successful MAS. Up to now, many QTL associated with SCN resistance have been effectively tagged with different molecular marker systems, including SSR, RAPD, RFLP and SNP [ 12 , 14 , 19 , 46 48 ]. However, no sequencing based mapping like GWAS for QTL or genes underlying the resistance to SCN has been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…An early study by Anand and Raoarelli ( 1989 ) indicated that at least one gene controls soybean resistance to HG 2.5.7. Thus far, at least 22 QTLs distributed on 10 chromosomes (1, 5, 6, 8, 10, 11, 15, 18, 19, and 20) have been associated with resistance to HG 2.5.7 (race 5; Yue et al, 2001a , b ; Guo et al, 2006a , b ; Wu et al, 2009 ; Vuong et al, 2010 ; Abdelmajid et al, 2014 ). Among these QTLs, genomic regions either containing or adjacent to the rhg1 locus on chromosome 18 have repeatedly been identified using different resistant soybean sources (Yue et al, 2001a ; Guo et al, 2006a , b ; Wu et al, 2009 ), suggesting the presence of highly important genes in this region that confer HG 2.5.7 resistance.…”
Section: Introductionmentioning
confidence: 99%
“…SCN_7_1 is an important QTL to SCN resistance for Handou 10. Some QTLs ( Webb et al, 1995 ; Ferreira et al, 2011 ; Abdelmajid et al, 2014 ; Chang et al, 2016 ; Vuong et al, 2015 ; Li et al, 2016 ) related to SCN resistance on chromosome 7 were reported at www.soybase.org . The physical location of SCN_7_1 was basically the same as the marker php02301a mapped in PI437654 ( Webb et al, 1995 ), but far from the QTLs detected by other researchers (see Footnote 2).…”
Section: Discussionmentioning
confidence: 99%